A WEB-BASED DECISION SUPPORT SYSTEM FOR THE QUALITY OF BIODIESEL - Eva Arifah, Dwi Setyaningsih dan Marimin (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACTThe main objectives of this research was to create a model of decision support systems for small industry of biodiesel that can be easier for biodiesel processors to manufacture biodiesel in accordance with standards. A web-based decision support systems for the quality of biodiesel models consisted of four models, namely the determination of biodiesel processing model producing the best decision in accordance with the characteristic of raw materials, the calculation the needs of additional ingredient in the biodiesel processing model producing the decision for the needs of the process, the determination of quality product model that produces the decision in accordance with quality standards, and analysis on the incompatibility of biodiesel quality model that generates suggestions for the user. The methodology used in this research was decision tree and rules based expert system. This research resulted in a simulation of web-based decision support systems for the biodiesel quality that aims to facilitate the processing of biodiesel, especially for small industries in producing biodiesel, and biodiesel that produced in accordance with the standard (SNI). Keywords: decision support systems, biodiesel, web-based, quality